THEOLOGICAL AND CULTURAL STUDIES ON INCEST FOR YOUTH CHRISTIAN - Mariani Harmadi; Karnawati; Dwi Anugrahani Handayani (Sekolah Tinggi Teologi Arastamar Bengkulu, 2023)
Incest is an iceberg phenomenon that is muted as it involves cultural, legal, economic, moral, psychological and human rights, where one and the other are interrelated, making it difficult to describe it. The purpose of this research is to observe the problem of incest from theological and cultural studies broadly concerning aspects of human life, both economic, social, educational, and biblical truth. The method used descriptive qualitative with theme analysis which will produce perspectives on incest broadly from cultural and theological studies based on Imago Dei's self-image, holiness and family according to God's design, the Creator of the household as a divine institution based on the Bible as the truth that absolute. The Old Testament records the emergence of cases of incest in the lives of the figures of faith which have the potential to cause ambiguity in adolescents, if Christian Education does not design the theme of incest in the curriculum as the context of teaching texts about holiness.